PENGARUH KONFLIK KERJA, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN - Tri Rahayu Ramadani; Evi Marlina; Siti Rodiah (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
This study aims to examine the effect of work conflict, reward and punishment on the performance of Cinter Stationery employees. This research uses a type of quantitative descriptive research. The population in this study are all employees who work at Cinter Stationery. The sampling method in this study used a non-probability sampling technique, namely saturated sampling with a total of 87 respondents. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear regression analysis method. The results of the study show that work conflict has a significant effect on employee performance, reward has an effect on employee performance and punishment has an effect on Cinter Stationery employee performance.